2020
DOI: 10.3390/cells9020449
|View full text |Cite
|
Sign up to set email alerts
|

MEG3 Promotes Differentiation of Porcine Satellite Cells by Sponging miR-423-5p to Relieve Inhibiting Effect on SRF

Abstract: Although thousands of long noncoding RNAs (lncRNAs) have been identified in porcine growth and development, the regulation mechanisms of functional lncRNAs have not been well explored. In this study, using 5′- and 3′-rapid amplification of cDNA ends (RACE) assays, we obtained two different variants of lncRNA maternally expressed gene 3 (MEG3), namely, MEG3 v1 and MEG3 v2, that were both highly expressed in porcine skeletal muscle and in the early stage of the differentiation of porcine satellite cells. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 68 publications
(90 reference statements)
2
20
0
Order By: Relevance
“…39 MEG3 activated by vitamin D suppresses glycolysis in cancer, 40 and MEG3 induces invasion of glioma cells via autophagy. 41 Moreover, MEG3 promotes differentiation of porcine satellite cells by sponging miR-423-5p 42 and is involved in pituitary tumor invasiveness. 43 In addition, MEG3 inhibits the inflammatory response of ankylosing spondylitis, 44 and MEG3 inhibits HMEC-1 cell growth and migration.…”
Section: Discussionmentioning
confidence: 99%
“…39 MEG3 activated by vitamin D suppresses glycolysis in cancer, 40 and MEG3 induces invasion of glioma cells via autophagy. 41 Moreover, MEG3 promotes differentiation of porcine satellite cells by sponging miR-423-5p 42 and is involved in pituitary tumor invasiveness. 43 In addition, MEG3 inhibits the inflammatory response of ankylosing spondylitis, 44 and MEG3 inhibits HMEC-1 cell growth and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic factors such as transcription factors, gene polymorphism, DNA methylation, and non-coding RNAs (ncRNAs) work together to control skeletal muscle development [45,46]. Recent studies have confirmed the essential roles of lncRNA in regulating skeletal muscle development [23][24][25]. However, the expression of lncRNAs in pigeon skeletal muscle remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of research aiming to construct lncRNA-associated ceRNA networks in myogenesis has been conducted [20,48,49]. The involvement of lncRNA as ceRNA in regulating animal skeletal muscle development has also been described [23][24][25]50,51].Therefore, constructing a ceRNA network may help elucidate the regulatory mechanisms underlying the development of pigeon skeletal muscle. In this study, we first identified 1625 DE lncRNAs, 573 DE miRNAs, and 11,311 DE mRNAs between muscle samples of different developmental ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, there have been significant advances in our understanding of the crucial roles of miRNAs and lncRNAs in regulating skeletal muscle development (Cesana et al, 2011;Legnini et al, 2014;Zhu et al, 2017;Kong et al, 2019;Cheng et al, 2020;Li et al, 2020). A limited number of studies have specifically identified roles of miRNAs and lncRNAs in muscular atrophy in cachexia and other diseases, and these studies suggest that miRNAs and lncRNAs are central to abnormal regulation of protein synthesis and degradation.…”
Section: Discussionmentioning
confidence: 99%